2018
DOI: 10.1021/acs.jpcb.8b10559
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Properties of Silver and Copper Ions in a Room Temperature Ionic Liquid: A First-Principles Study

Abstract: Understanding the behavior of metal ions in room temperature ionic liquids (ILs) is essential for predicting and optimizing performance for technologies like metal electrodeposition; however, many mechanistic details remain enigmatic, including the solvation properties of the ions in ILs and how they are governed by the intrinsic interaction between the ions and the liquid species. Here, we utilize first-principles molecular dynamics simulations to unravel and compare the key structural properties of Ag+ and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Due to a suite of attractive and widely tunable physiochemical properties, roomtemperature ionic liquids (ILs) have emerged as highly promising electrolytes in a wide range of technologies, including catalysis, 1 ion batteries, 2 CO2 capture, 3 electrodeposition, [4][5][6] and supercapacitors. 7,8 Both experimental and computational studies highlighted that understanding the detailed structure and arrangement of ions in porous electrodes is essential for optimizing performance for many of these applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to a suite of attractive and widely tunable physiochemical properties, roomtemperature ionic liquids (ILs) have emerged as highly promising electrolytes in a wide range of technologies, including catalysis, 1 ion batteries, 2 CO2 capture, 3 electrodeposition, [4][5][6] and supercapacitors. 7,8 Both experimental and computational studies highlighted that understanding the detailed structure and arrangement of ions in porous electrodes is essential for optimizing performance for many of these applications.…”
mentioning
confidence: 99%
“…Due to a suite of attractive and widely tunable physiochemical properties, room-temperature ionic liquids (ILs) have emerged as highly promising electrolytes in a wide range of technologies, including catalysis, ion batteries, CO 2 capture, electrodeposition, and supercapacitors. , Both experimental and computational studies highlighted that understanding the detailed structure and arrangement of ions in porous electrodes is essential for optimizing performance for many of these applications. A prime example by Chmiola et al indicated that an optimal capacitance is achieved when ion size matched that of the pore, which was attributed to distortion of the ion solvation under spatial confinement. , However, since this initial discovery, detailed and comprehensive structural insights have been slow to evolve, because electrolyte behavior at interfaces and under confinement is challenging to resolve. These characteristics are especially intractable for emergent electrolytes like ILs, which exhibit bulky, flexible, and widely varying molecular configurations.…”
mentioning
confidence: 99%